(untitled) (Fiep Bulletin - online, 2012)
Sport is a phenomenon which is assuming increasingly greater importance in today’s society. It is a product and at the same time an event that transforms the culture into which it is introduced. It is developed based on a variety of areas of knowledge, the so-called Sports Sciences. As part of this set of disciplines, sport psychology has been experiencing the demands of this area of involvement in the sense of contributing towards the optimization of athlete performance in at least the four basic skills required for practicing it at high levels: Physical, Technical, Tactical and Emotional. Accordingly, the main aim of this study is to present several forms of intervention by the sports psychologist in the context of high-performance sport. It is maintained that sports training integrates psychological preparation with physical, technical and tactical preparation since it is believed that the psychological conditions are most likely to be directly associated with the development of each one of these abilities. In this perspective, a new field of involvement can be observed for sport psychology: the contribution to the optimization of sporting performance where the psychology professional gets to be another member of the technical team, working in conjunction with the other professionals, in the day-to-day realities of the team. This contribution is realized by means of psychological assessment and a psychological preparation and contributes towards long-term results. Therefore it is a question of an integration that differs from that usually observed in sporting teams, in which the psychologist carries out instant interventions or opportune actions in specific situations